Evaluation of small business failure and the framing problem. (16th April 2009) - Stanton, Patricia; Tweed, David
By examining the extant literature evaluating small business failure, this paper seeks to show that research in the area has been 'framed', leading to predictable outcomes. Presentation (framing) blinkers the way a problem is perceived and reviewed. Positive labels are more likely to evoke positive associations; negative labels are more likely to evoke negative associations leading to evaluations dependent on how the situation has been labelled. Much prior literature has focused on the negative area of small business failure. An established framework is used to analyse and illustrate that framing has occurred within that literature with respect to assessment of small business failure. Many researchers have accepted that small business is likely to fail with the result that their research is aimed at supporting this contention. Such acceptance impacts on policy decisions and decisions of venture capitalists, bankers and potential entrepreneurs.